Late Ediacaran crustal thickening in Iran: Geochemical and isotopic constraints from the ~550 Ma Mishu granitoids (northwest Iran). Issue 7 (19th May 2017) - Shahzeidi, Malihe; Moayyed, Mohsen; Murata, Mamoru; Yui, Tzen-Fu; Arai, Shoji; Chen, Fukun; Pirnia, Tahmineh; Ahmadian, Jamshid
ABSTRACT: The aim of this article is to examine the geochemistry and geochronology of the Cadomian Mishu granites from northwest Iran, in order to elucidate petrogenesis and their role in the evolution of the Cadomian crust of Iran. The Mishu granites mainly consist of two-mica granites associated with scarce outcrops of tonalite, amphibole granodiorite, and diorite. Leucogranitic dikes locally crosscut the Mishu granites. Two-mica granites show S-type characteristics whereas amphibole granodiorite, tonalities, and diorites have I-type signatures. The I-type granites show enrichment in large-ion lithophile elements (e.g. Rb, Ba and K) and depletion in high field strength elements (e.g. Nb, Ti and Ta). These characteristics show that these granites have been formed along an ancient, fossilized subduction zone. The S-type granites have high K, Rb, Cs (and other large ion lithophile elements) contents, resembling collision-related granites. U–Pb zircon dating of the Mishu rocks yielded 238 U/ 206 Pb crystallization ages of ca. 550 Ma. Moreover, Rb–Sr errorchron shows an early Ediacaran age (547 ± 84 Ma) for the Mishu igneous rocks. The two-mica granites (S-type granites) show high 87 Sr/ 86 Sr(i) ratios, ranging from 0.7068 to 0.7095. Their ɛ Nd values change between −4.2 and −4.6. Amphibole granitoids and diorites (I-type granites) are characterized by relatively low 87 Sr/ 86 Sr(i) ratios (0.7048–0.7079) and higher values of ɛ Nd (−0.8 to −4.2). Leucogranitic dikes have quite juvenile signature, with ɛ Nd values ranging from +1.1 to +1.4 and Nd model ages (TDM ) from 1.1 to 1.2 Ga. The isotopic data suggests interaction of juvenile, mantle-derived melts with old continental crust to be the main factor for the generation of the Mishu granites. Interaction with older continental crust is also confirmed by the presence of abundant inherited zircon cores. The liquid-line of descend in the Harker diagrams suggests fractional crystallization was also a predominant mechanism during evolution of the Mishu I-type granites. The zircon U–Pb ages, whole rock trace elements, and Sr–Nd isotope data strongly indicate the similarities between the Mishu Cadomian granites with other late Neoproterozoic–early Cambrian (600–520 Ma) granites across Iran and the surrounding areas such as Turkey and Iberia. The generation of the Mishu I-type granites could be related to the subduction of the Proto-Tethyan Ocean during Cadomian orogeny, through interaction between juvenile melts and old (Mesoproterozoic or Archaean) continental crust. The S-type granites are related to the pooling of the basaltic melts within the middle–upper parts of the thick continental crust and then partial melting of that crust.